VALIDITAS DAN RELIABILITAS DALAM EVALUASI PAI - Faiqotun nisa; Bashiratud Diyana Basy; Ahmad Jauhari; Yahya Mof; Hasni Noor (TARBIYAH DARUSSALAM: JURNAL ILMIAH KEPENDIDIKAN DAN KEAGAMAAN, 2026)
Validity and reliability are two fundamental aspects that determine the quality of educational evaluation instruments. A valid instrument accurately measures the intended competencies, while a reliable instrument produces consistent and trustworthy results. This study aims to examine the concepts of validity and reliability of educational evaluation instruments and their implications for Islamic Religious Education (IRE). The study employed a qualitative approach using a library research method. Data were collected from primary and secondary sources, including books, scientific journals, and other relevant academic publications. Data analysis was conducted using content analysis through the stages of data reduction, data presentation, interpretation, and conclusion drawing. The findings indicate that instrument validity consists of content validity, construct validity, and criterion-related validity, all of which ensure measurement accuracy. Meanwhile, reliability refers to the consistency of measurement results and can be assessed through test-retest, split-half, Cronbach’s Alpha, and Kuder-Richardson (KR-20 and KR-21) techniques. The study also reveals that the quality of evaluation instruments is influenced by factors such as the number of test items, difficulty level, scoring objectivity, construct homogeneity, and score distribution. Therefore, validity and reliability testing should be systematically implemented to produce accurate, objective, and accountable evaluation instruments in the learning process of Islamic Religious Education.